Regulation of birthweight by placenta-derived miRNAs: evidence from an arsenic-exposed birth cohort in Bangladesh. Issue 6 (3rd June 2018) - Rahman, Mohammad L.; Liang, Liming; Valeri, Linda; Su, Li; Zhu, Zhaozhong; Gao, Shangzhi; Mostofa, Golam; Qamruzzaman, Qazi; Hauser, Russ; Baccarelli, Andrea; Christiani, David C.
ABSTRACT: Altered expression of microRNAs (miRNAs) is implicated in fetal growth. However, the mechanisms by which placenta-derived miRNAs regulate birthweight are not well understood. In Phase 1, we compared the expression of 754 miRNAs in the placenta from two extreme birthweight groups (0.8–2.2 kg vs. 3.3–3.9 kg, n = 77 each) selected from an arsenic-exposed Bangladeshi birth cohort (n = 1, 141). We identified 49 miRNAs associated with the extreme birthweight groups and/or gestational age in Phase 1, which were further analyzed in Phase 2 among 364 randomly selected mother-infant pairs. Gestational age was determined by ultrasound. Causal mediation analysis was used to estimate the effect of miRNAs on birthweight considering gestational age a mediator, adjusting for cord blood arsenic and other risk factors. miR-1290, miR-195, and let-7g showed significant inverse associations with gestational age, while miR-328 showed significant positive association [false discovery rate (FDR) <0.05]. Via changing gestational age, miR-1290, miR-195, and miR-27a showed significant inverse associations with birthweight, while miR-328 and miR-324-5p showed significant positive associations (FDR <0.05). The effect of miRNAs on birthweight varied by gestational age (for miR-1290, miR-195, miR-328) and in utero arsenic exposure (for miR-1290): stronger effect was observed among infants delivered early in gestation or exposed to higher concentrations of arsenic in cord blood. Gene enrichment analysis with in silico predicted targets identified cell proliferation, inflammation, apoptosis, insulin, and IGF family signaling cascades associated with these miRNAs. Future studies are warranted to replicate these findings and assess these miRNAs as early biomarkers of fetal growth.